Critical and Analytical Study of the "2023 ke muntakhib Afsane" - Khurshid, Raheela; Salma; Gul, Kainat (sourcecoder, 2024)
The selected short stories of 2023, "Qurrat-ul-Ain Ainie" and "Kiran abbas Kiran," constitute a curated anthology of 23 distinguished narratives, including contributions from exemplary storytellers. From an artistic perspective, a study of this book reveals plots that are intricately crafted and well-developed, and characters whose psychologies are precisely portrayed. There is a profound correlation between the themes and titles, while the language and expression exhibit refinement, eloquence, and adherence to literary rules and norms, captivating the reader’s attention. Similarly, from an intellectual standpoint, the stories in this book highlight societal and psychological dimensions, examining the proliferation of evils in society through the prism of characters’ psyches. In both artistic and intellectual dimensions, this anthology stands as a resounding testament to the artistic prowess of the storytellers.